Innovation, technical change and patents in the development process: A long term view - Mario Cimoli; Giovanni Dosi; Roberto Mazzoleni; Bhaven Sampat (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2011)
An essential aspect of catching up by developing countries is the emulation of technological leaders and the rapid accumulation by individuals and organizations of the knowledge and capabilities needed in order to sustain processes of technical learning. The rates and patterns of development of such capabilities are fundamentally shaped by the opportunities that indigenous organizations have to enter and operate in particular markets and technology areas. However, knowledge accumulation is also influenced by the governance of intellectual property rights (IPRs). The purpose of this work - prepared for a volume of the Initiative for Policy Dialogue, Columbia University, Intellectual and Property Rights Taskforce - is to offer an assessment of such influences in the long term, beginning with the early episodes of industrialization all the way to the present regime. The historical record is indeed quite diverse and variegated. However if there is a robust historical fact, it is the laxity or sheer absence of intellectual property rights in nearly all instances of successful catching up. We begin by reviewing a few theoretical arguments that economists have formulated on the effects of a system of patent protection. We will then review the historical evidence on the roles of patents in economic development. Next we discuss the changes in the IPR regime that have taken place roughly over the last third of a century in the United States. The reason for focusing on the United States is that doing so will outline the broad template of patent policy reform that has been adopted by policy makers in many other countries as a result of a varying mix of external pressures, myopia, corruption and ideological blindness. The final part of this essay, explores the likely impact of harmonization of international patent laws - including TRIPS - on developing countries.
Keywords: 330; Intellectual Property Rights; Catching-up; Imitation; Development; TRIPS